Coda: the interactional affordances and constraints of technology-rich teaching and learning environments. Issue 2 (3rd April 2022) - Thorne, Steven L.; Hellermann, John
ABSTRACT: This coda describes various affordances and constraints associated with technology-rich language teaching and learning. It begins with a discussion of articles in this special issue of Classroom Discourse and then expands to engage with broader dynamics associated with uses of digital tools in language education. In particular, we address research issues relating to technology-rich activity such as the complexity of multimodal transcription and analysis when mapping multiple semiotic fields, potential challenges presented by polyfocality, the implications of response latency on the sequential organisation of talk, the historically and experientially formed cultures-of-use of digital communication tools as they may inform patterns and expectations of behaviour, and the potentially active role of various technologies as co-constitutive of the morphologies of action of teachers and learners in technology-rich settings.